Dietary Exposure Assessment and Contaminants Biomonitoring in the Dehcho Region, Northwest Territories: Exploring the Relationship Between Mercury Exposure, Omega-3 Fatty Acid Status, and Fish Consumption - Laird, Matthew (University of Waterloo, 2017)
Background: Fish are often rich in essential micronutrients including omega-3 fatty acids (FA), and are a cultural and dietary staple in traditional food systems of First Nations communities in the Canadian subarctic. Country foods including fish contribute to improved food security, and promote the cultural sovereignty of First Nations communities. However, these foods are often a primary route of exposure to methylmercury, an environmental contaminant that can pose significant adverse health risks. Objectives: The objectives of this study are to: 1) Determine the concentration of total mercury (Hg) and long chain omega-3 polyunsaturated fatty acids (omega-3 PUFAs) in the muscle tissue of various wild-caught freshwater fish species harvested from eight lakes in the Dehcho region, Northwest Territories (NWT); 2) Construct a probabilistic, population-based retrospective dose reconstruction model to assess dietary omega-3 PUFA intake and Hg exposure across several Dehcho First Nations communities; 3) Characterize and quantify sources of mercury and omega-3 PUFA exposure from country food consumption, and identify key contributors from the diet; and 4) Assess the utility and accuracy of the probabilistic exposure model at estimating population-level profiles of risk and cardioprotective benefit using biomarkers for omega-3 PUFAs in blood plasma and Hg in hair. Methods: Samples from eight freshwater fish species [Burbot (Lota lota; also known as Loche or Mariah), Cisco (Coregonus artedi; also known as Herring), Lake Trout (Salvelinus namaycush), Lake Whitefish (Coregonus clupeaformis), Longnose Sucker (Catostomus catostomus), Northern Pike (Esox lucius; known locally as Jackfish), Walleye (Sander vitreus; also known as Pickerel) and White Sucker (Catastomus commersoni)] were harvested from eight lakes of the Dehcho (including Ekali, Trout, Sanguez, Tathlina, McGill, Gargan, Mustard, and Kakisa Lakes) in August of 2013, 2014, and 2015. Omega-3 PUFA levels in fish tissue were determined by a lipid extraction on ...